Perancangan Strategi Periklanan dengan Konten Social Media Marketing Menggunakan Instagram @asyraaf_official pada UMKM Asyraaf Official Store Tahun 2023 - Zoehirfan, Muhammad Farel; Wulandari, Astri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Advertising is a way to promote products or services to the public in various ways according to the provisions contained therein. Using advertising in the form of product promotion will make it easier for sellers to market their products. Advertising is a strategy to promote a product or service that is being sold, with an advertisement provided by a company, will make it easier for the audience to find out about the product being sold. The purpose of this design is how to design content design for Muslim fashion products uploaded via the Instagram platform. This is made as a form of information to the public that wearing Muslim clothing is not something to be ashamed of and can still look stylish. Research in this design uses qualitative methods and uses data analysis methods from the results of interviews and then developed into a hypothesis. The results of the design given are in the form of photos and designs in the form of an Instagram feed whose function is to make people from all walks of life more interested in wearing Muslim clothing. Keywords: Advertising, Content Marketing, Instagram, Social Media